2017
DOI: 10.1111/cico.12254
|View full text |Cite
|
Sign up to set email alerts
|

Examining Neighborhood Opportunity and Locational Outcomes for Housing Choice Voucher Recipients: A Comparative Study between Duval County, Florida, and Bexar County, Texas

Abstract: Recent attention has highlighted the importance of providing low‐income households access to opportunity‐rich neighborhoods. Using a neighborhood opportunity framework developed specifically for the Housing Choice Voucher (HCV) program, this study investigates whether low‐income households participating in the program live in opportunity areas. The results indicate that with scarce high‐opportunity neighborhoods, most HCV households reside in mixed opportunity areas and face tradeoffs when deciding where to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This finding may not be detrimental if neighbourhoods are viewed through the lens of tradeoff attributes, as documented by recent literature on neighbourhood opportunity (e.g. Walter and Wang, 2016; Wang et al, 2017). Specifically, neighbourhoods in or near urban centres that are relatively high in poverty have transportation accessibility in Florida (Walter et al, 2015, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…This finding may not be detrimental if neighbourhoods are viewed through the lens of tradeoff attributes, as documented by recent literature on neighbourhood opportunity (e.g. Walter and Wang, 2016; Wang et al, 2017). Specifically, neighbourhoods in or near urban centres that are relatively high in poverty have transportation accessibility in Florida (Walter et al, 2015, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…Only with respect to escaping high-crime neighborhoods are voucher holders' outcomes indisputably positive (Lens, Ellen, and O'Regan 2011). Using a complex "neighborhood opportunity framework" with 32 indicators in four categories, Wang et al (2017) concluded that when high-opportunity neighborhoods are scarce-as McClure ( 2010) has shown they are-voucher households reside in areas with "moderate or poor accessibility and neighborhood conditions compared to other. .…”
Section: What Change Means For "Opportunity Neighborhoods"mentioning
confidence: 99%